Risk factors associated with a past history of Exercise Associated Muscle Cramps (EAMC) in Ironman triathletes : a case control study - Shang, Gavin Sam (MRC/UCT RU for Exercise and Sport Medicine, 2014)
Includes bibliographical references (p. 70-73).